A mathematical optimization model for allocating physical spaces to academic requirements - Zeynab Rashidi; Zahra Rashidi (تصمیم گیری و تحقیق در عملیات)
Purpose: The problem of allocating space to academic needs is one of the complex optimization issues that distributes a limited set of educational and research needs to a set of resources with a set of constraints. Due to the complexity of this problem, several techniques based on innovative methods have been proposed. In this paper, a mathematical model of integer programming is presented to formulate this problem.Methodology: To solve the model, the gradient descent method is used and its parameters are adjusted. To evaluate the proposed model and solution, the data and facilities of one of the fledgling faculties at Allameh Tabatabai University in Tehran are tested. There are 11 requirements and 18 allocable spaces in this faculty and therefore there are 198 binary decision variables, in the model. In experiments, several scenarios are created and the results of each scenario are compared.Findings: The proposed model and solution is a general method and can be used for other faculties and universities that face space constraints.Originality/Value: In this article, a mathematical model was presented to formulate the problem of allocating space, which is one of the important decision-making issues for organizations and research educational institutions.